Phytochemical constituents, hypoglycemic and haematological effects of methanolic Acalypha wilkesiana leaves extract on streptozotocin-induced diabetic rats - El-Khateeb, Ayman Yahya; Azzaz, Nabil Abdel-Khalik Eid; Mahmoud, Hemdan Ibrahem (European Journal of Chemistry, 2014)
Recently, there has been more interest with antidiabetic agents commencing natural products from plants as a better treatment than currently used synthetic drugs. The high performance liquid chromatography analysis of methanolic Acalypha wilkesiana leaves extract revealed occurrence of twenty one polyphenolic compounds. Catechin is the main constituent (29.91%), followed by apigenin (20.96%), then, ellagic acid, quercetin, kampferol, ferulic acid, luteolin, pyrogallol, rutin, caffeic acid, chlorogenic acid, protocatechouic acid, p-coumaric acid, caffiene, syrigic acid, catechol and p-OH-benzoic acid in percentages of 17.54, 10.45, 7.63, 4.67, 4.61, 4.30, 3.21, 3.15, 2.10, 1.48, 1.43, 1.13, 1.09, 1.08 and 1.05%, respectively. The antidiabetic and heamatological effects of methanolic Acalypha wilkesiana leaves extract (10, 20 and 40 mg/100 g body weight) in streptozotocin diabetic rats were investigated comparing with metformin HCl (50 mg/100 g body weight) for 30 days. Our results indicated that the most effective dose of methanolic Acalypha wilkesiana leaves extract was 40 mg/100 g body weight, which decreased blood glucose level to about 77.37% in diabetic rats, compared with a percentage of 76.50% achieved by administration with metformin HCl. Furthermore, liver functions activity, kidney functions, lipid profile, atherogenic indices and haematological parameters were scrutinized in diabetic rats treated with methanolic Acalypha wilkesiana leaves extract. These results indicate that the methanolic leaves extract of Acalypha wilkesiana, have favorable effects in bringing down the severity of diabetes and justify its use in traditional medicine for the treatment of diabetes and its complications.